La organización del conocimiento en el Nuevo Orden Transcultural: del totalitarismo a la desclasificación (la razón como creencia y la oc como burocracia) - GARCIA GUTIÉRREZ, Antonio (Faculdade de Filosofia e Ciências, 2014)
Starting from the traditional conception of classification, with an emphasis on its role as exomemory, but warning of the dangers of the symbolic violence, this article analyzes two dimen-sions that complement each other; reason as a belief and knowledge organization as bureaucracy for a subsequent approach to the epistemic obstacles to a cross-cultural dimension that subsidizes what might be called declassification, while adopting a complex approach that does not exclude any pre-, post- or para- epistemological tool.